Osteoarthritis and Depression Update: 2023-Can the Stress and Coping Model Help? - Ray Marks (Journal of Aging Research And Healthcare, 2023)
Background Osteoarthritis and depression are both key barriers to healthy aging and greatly heighten the risk for many negative health issues that seriously impact life quality. When combined what are the implications? Aim This mini review examines 2023 data pertaining to osteoarthritis and depression and older adults and a possible theoretical framework of stress that may direct our approaches in the future. Methods and Procedures Articles published between January 1 and August 15 2023 that addressed the current topic of interest and that were extracted from PUBMED, PubMed Central, Science Direct, and Google Scholar were carefully read and their key points arepresented in narrative form. Results As in the past, very few tangible theory-based prospective analyses that employ valid measures of depression and examine any association of any form of osteoarthritis longitudinally and in a consistent manner prevail. Several reports use the same or similar large cohort to draw upon, and find various degrees of clinical implications, but this may not embrace the need for more inclusivity, sampling strategies, control and diversity issues, as well as embracing the role of cognitions positive and negative. Conclusion Without efforts to develop sound research designs of diverse and carefully differentiated osteoarthritis substantive samples it is impossible to delineate the origin or implications of the osteoarthritis-depression linkage reported currently or arrive at a deep understanding of its relevance, to life quality and public health costs. What is needed to protect against or minimize either or both these clinically related disabling correlates in the aged population warrants timely study.
Keywords: Depression